2015
DOI: 10.1007/s00011-015-0893-y
|View full text |Cite
|
Sign up to set email alerts
|

FK506 reduces albuminuria through improving podocyte nephrin and podocin expression in diabetic rats

Abstract: Objective and designSeveral works in the setting of early experimental diabetic nephropathy using anti-inflammatory drugs, such as the calcineurin inhibitor FK506, have shown prevention of the development or amelioration of renal injury including proteinuria. The exact mechanisms by which anti-inflammatory drugs lower the albuminuria have not been still clarified well.MaterialsThe diabetic rats were induced by using streptozotocin.TreatmentThe diabetic rats were subjected to oral FK506 treatment at a dose of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
(34 reference statements)
2
31
0
Order By: Relevance
“…Along with the results of these studies, several studies have investigated the mechanisms of tacrolimus in reducing proteinuria. Tacrolimus was considered to have multifocal mechanisms for reducing proteinuria, such as immunosuppressive mechanisms by suppression of the nuclear factor of activated T cell activity in podocytes [ 17 , 18 ], intraglomerular hemodynamic changes [ 19 21 ], inhibition of the vascular permeability factor [ 22 ], and a direct effect on podocytes [ 8 10 , 23 , 24 ]. Among these mechanisms, we suggested that the early anti-proteinuria effect of tacrolimus was due to reversible hemodynamic changes rather than to other structural changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the results of these studies, several studies have investigated the mechanisms of tacrolimus in reducing proteinuria. Tacrolimus was considered to have multifocal mechanisms for reducing proteinuria, such as immunosuppressive mechanisms by suppression of the nuclear factor of activated T cell activity in podocytes [ 17 , 18 ], intraglomerular hemodynamic changes [ 19 21 ], inhibition of the vascular permeability factor [ 22 ], and a direct effect on podocytes [ 8 10 , 23 , 24 ]. Among these mechanisms, we suggested that the early anti-proteinuria effect of tacrolimus was due to reversible hemodynamic changes rather than to other structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…The lower UPCR in the Tac group compared to the non-Tac group during the trial phase despite the later cr has recovery, is difficult to explain solely by hemodynamic changes. Therefore, the rapid decrease of proteinuria in the early stage may be due to hemodynamic changes, but the overall decrease may be the combination of the various mechanisms mentioned above [ 16 23 ]. Time-averaged proteinuria is the most reliable predictor of kidney survival [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have found that the mutation, deletion and abnormal expression of podocyte proteins, especially nephrin and podocin, play an important role in glomerulopathy and proteinuria . Tacrolimus's mechanism that protects glomerular podocytes and reduces urinary protein may be associated with up‐regulation of nephrin and podocin expression . However, the expression changes of these podocyte proteins in different pathological types of glomerular diseases are inconsistent .…”
Section: Discussionmentioning
confidence: 99%
“…[102][103][104] Tacrolimus's mechanism that protects glomerular podocytes and reduces urinary protein may be associated with up-regulation of nephrin and podocin expression. 105,106 However, the expression changes of these podocyte proteins in different pathological types of glomerular diseases are inconsistent. 107,108 Another possible reason for different remission rates in different studies is whether the relapses of glomerular disease has been observed.…”
Section: Discussionmentioning
confidence: 99%